Micelle-templated carbon coatings and their applications for catalysis - Chuenchom, Laemthong; Justus Liebig University Giessen (My University, 2013)
The aim of this thesis was to develop synthesis methods for catalytically active carbon coatings with controlled pore structure. The synthesis strategy is based on evaporation-induced self-assembly (EISA) and soft-templating principles using resorcinol-formaldehyde (RF) as a carbon precursor and amphiphilic block-copolymers as structure-directing soft-templates. The main goal was to obtain a desirable 3D pore morphology on different substrates. Hence, synthesis procedures for bulk mesoporous carbon powders prepared under acidic conditions were refined and adapted to surface coatings. The synthesis yielded porous crack-free carbon films with pore sizes depending on the employed pore template. Films templated with F127 possessed a contracted 3D cubic mesostructure (Im3m) with pores of about 8 nm width and 4 to 6 nm height. The film thickness (measured after carbonization at 600°C) could be increased up to about 820 nm by increasing the withdrawal speed of dip-coating while retaining the mesostructure. The films templated with F127 possess high surface areas up to 520 m2/cm3 (BET) and pore volumes up to 0.45 cm3/cm3. Templating with different polymers (PIB-PEO 3000 as well as 10k-PB polymers) resulted in increased pore diameters up to 20 nm (measured in the direction parallel to the substrate). Also here, an increase in withdrawal speed of dip-coating increased the film thickness up to 640 nm. However, thicker films templated with PIB-PEO 3000 exhibited a reduced degree of mesopore order.In order to synthesize mesoporous carbon films containing catalytically active metal particles the synthesis procedure was extended to incorporate also appropriate Pd and Pt precursors. The synthesis employing F127 as a template yielded high quality, uniform mesoporous carbon coatings containing either Pd or Pt particles. Pd loading as high as 3 wt% were successfully reached. The Pd/C films carbonized at 600°C possess a contracted Im3m mesopore structure with uniform pore sizes of ~8 nm in the direction parallel to the substrate and ~6 nm in the direction perpendicular to the substrate. A thickness of ~400 nm, a surface area of 587 m2/cm3 (BET) and well-distributed Pd particles with a uniform size of ~15 nm were obtained. The synthesis procedure for mesoporous Pd/C catalyst films was then adapted to coat also steel plates, which are typically used as substrates in a catalytic reactor. The facile and reproducible synthesis of these catalyst coatings allowed for up scaling up to 25 steel plates with identical features for both mesopore structure and Pd particles. The Pd-containing mesoporous carbon coatings on the steel plates were tested as catalysts for gas-phase hydrogenation of 1,3-butadiene. The Pd/C catalyst coatings proved to be highly active and selective with conversions of up to 80% at a reaction temperature of 80°C and high selectivity to butenes of up to ~95%.

Das Ziel dieser Arbeit war es Synthesemethoden für katalytisch aktive Kohlenstoffbeschichtungen mit kontrollierter Porenstruktur zu entwickeln. Die Synthesestrategie basiert auf der verdampfungsinduzierten Selbstorganisation (engl. evaporation-induced self-assembly, EISA) mit einer Resorcin-Formaldehydverbindung als Kohlenstoffquelle und amphiphilen Blockcopolymeren als strukturdirigierende Template. Der Schwerpunkt dieser Arbeit war es eine dreidimensionale Porenstruktur mit vernetzten Poren auf verschiedenen Substraten zu erhalten. Dazu wurde eine Synthesevorschrift für mesoporösen Kohlenstoff, synthetisiert in Pulverform, unter sauren Bedingungen adaptiert und weiterentwickelt. Es wurden poröse, rissfreien C-Filme erhalten mit Porengrößen, die abhänging vom verwendeten Templat waren. Mit Pluronic F127 templatierte Filme besaßen eine kontrahierte kubische 3D-Mesostruktur (Im3m) mit Poren von 8 nm Breite parallel und 4 bis 6 nm Höhe normal zum Substrat. Die Schichtdicke (gemessen nach der Karbonisierung bei 600 °C) konnte bei schnellem Herausziehen des Substrates auf bis zu 820 nm erhöht werden, unter Beibehaltung der Mesostruktur. Die F127-templatierten Filme zeigten eine BET-Oberfläche von bis zu 520 m2/cm3 und ein Porenvolumen bis zu 0.45 cm3/cm3.Die templatierte Porengröße (parallel zum Substrat) konnte auf etwa 20 nm erhöht werden durch Verwendung verschiedener Polymere (PIB-PEO 3000 und 10k-PB Polymeren).Auch hier konnte bei Wahl einer hohen Ziegeschwindigkeit eine Filmdicke von bis zu 640 nm realisiert werden. Jedoch verringert sich der Grad der Porenordnung mit ansteigender Schichtdicke.Um mesoporöse C-Filme mit katalytisch aktiven Metallpartikeln zu erzeugen, wurden Pd- oder Pt-Vorläufer in die Syntheseprozedur integriert. Eine Synthese mit F127 als Porentemplat führte zu einheitlichen mesoporösen Kohlenstoffschichten, die Pd- bzw. Pt-Partikeln enthielten. Eine Pd-Beladung von bis zu drei Gewichtsprozenten konnte erreicht werden. Die Filme besaßen eine kontrahierte Im3m Porenstruktur mit einer einheitlichen Porengröße von etwa 8 nm parallel und etwa 6 nm normal zum Substrat. Die Schichtdicke betrug etwa 400 nm und die BET Oberfläche etwa 587 m2/cm3. Die homogen in der Schicht verteilten Pd-Partikeln besaßen eine gleichmäßige Größe von ungefähr 15 nm. Pd-haltige mesoporöse C-Filme wurden auch auf Stahlsubstraten abgeschieden und diese Platten als Katalysatoren in einem Reaktor verwendet. Die einfache und reproduzierbare Synthesemethode ermöglichte ein Up-Scaling auf bis zu 25 Stahlplatten mit gleicher Mesoporenstruktur und Pd-Partikelgröße.Die Pd-haltigen mesoporösen C-Schichten auf Stahlsubstraten wurden in der Hydrierungsreaktion von 1,3-Butadien in der Gasphase katalytisch getestet. Die Katalysatoren zeigten eine hohe Aktivität mit Umsätzen bis zu 80% bei einer Reaktionstemperatur von 80°C sowie eine hohe Selektivität zu Butenen von bis zu 95%.
Mizellen-templatierte Kohlenstoffbeschichtungen und ihre Anwendung in der Katalyse
Keywords: Kohlenstoffbeschichtungen; Mizellen; Katalyse; Mesoporous Carbons; Coatings; Micelles; Templating; Catalysis; ddc:500